2022
DOI: 10.3390/dj10100177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multibracket Orthodontic Treatment versus Clear Aligners on Periodontal Health: An Integrative Review

Abstract: Objective: This integrative review aimed to identify studies comparing the periodontal health in patients wearing multibracket orthodontic appliances and clear aligners. Materials and methods: An integrative literature search was performed through different databases, PubMed/Medline, PMC, and the Cochrane Library. This work was submitted to a search strategy following the PICO method and included the focus question: “Could the chosen orthodontic appliance change significantly the oral hygiene of the patient, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this regard, we opted for a slower movement stage (0,15 mm/1°) along with specific design features (see below) to obtain good periodontal results (26,30). Clear aligners are claimed as a better solution for maintaining periodontal health conditions compared to fixed appliances, due to better management of daily oral hygiene maneuvers (31). The patient found it beneficial to be able to remove the aligners and maintain her oral hygiene routine without the encumbrance of fixed components of the conventional orthodontic appliance.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we opted for a slower movement stage (0,15 mm/1°) along with specific design features (see below) to obtain good periodontal results (26,30). Clear aligners are claimed as a better solution for maintaining periodontal health conditions compared to fixed appliances, due to better management of daily oral hygiene maneuvers (31). The patient found it beneficial to be able to remove the aligners and maintain her oral hygiene routine without the encumbrance of fixed components of the conventional orthodontic appliance.…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of orthodontic treatments performed with CA, [28] in which the occlusal coverage prevents the obtention of natural contacts, has become a crucial research topic in Dentistry, [29] more specifically in the orthodontic community. The presence of the CA material in the interocclusal space may lead to anatomical changes and difficulties that are inherent to the obtention of those contacts and therefore compete against the final goal of CAT [1,7,8,13].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with what Jiang et al 11 and Oikonomou et al 14 previously reported, highlighting significantly lower plaque index scores in CA patients. An integrative review performed by Partouche et al 13 concluded that CA patients were less subject to plaque accumulation than FA patients. However, among all the indexes evaluated, only PI differed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Recent evidence from systematic reviews suggests that patients in treatment with CAs show better periodontal health indicators than those wearing traditional braces. [11][12][13] However, the level of evidence of the articles included in the qualitative or quantitative synthesis was low due to the risk of bias and heterogeneity in the selected studies. 11 White spot lesions (WSLs) are a major concern when dealing with orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%